Evaluating the therapeutic efficacy of 595 nm pulsed dye laser system for treating capillary malformations - Domenico Piccolo; Chiara Retrosi; Irene Fusco; Tiziano Zingoni; Claudio Conforti (Dermatology Reports)
Capillary malformations are the most prevalent low-flow vascular abnormalities. A case of a 30-year-old woman with lateral capillary malformation was presented in this case report. Dermoscopic showed erythematous background and rare telangiectasic vessels for less than 5-10% of the entire area examined. She underwent a single treatment with a 595 nm pulsed dye laser. Excellent response at the end of the session and a clear reduction of the capillary malformation at clinical follow-up 2 months later was achieved. Dermatoscopic and 3D photographic evaluation before and after laser treatment also documented the disappearance of the erythematous background and telengectasic vessels.